One-pot oxidation of secondary alcohols to alpha-hydroxy ketones: application to synthesis of oxoaplysinopsin D, E, F, & G - Kulkarni, Akshay S.; Ramesh, Eagala; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
A simple one-pot transformation of secondary alcohols to alpha-hydroxy ketones using pyridinium dichromate (PDC) in DMF has been developed and substrate scope tested with 25 compounds of hydantoin derivatives. Using this method, we have devised a common dihydroxy intermediate and synthesized four natural products oxoaplysinopsins D, E, F, and G for the first time.
Keywords: alpha-Hydroxylation; Hydantoin; Natural product; Oxoaplysinopsin; Retro-aldol